2023
DOI: 10.1017/s0033291723002854
|View full text |Cite
|
Sign up to set email alerts
|

Neural activations during cognitive and affective theory of mind processing in healthy adults with a family history of alcohol use disorder

F. Schmid,
A. Henry,
F. Benzerouk
et al.

Abstract: Background Social cognition impairments are a common feature of alcohol use disorders (AUD). However, it remains unclear whether these impairments are solely the consequence of chronic alcohol consumption or whether they could be a marker of vulnerability. Methods The present study implemented a family history approach to address this question for a key process of social cognition: theory of mind (ToM). Thirty healthy adults with a family history of AUD (FH+) and 30 healthy adults with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Few studies have explored common SC components (i.e., emotion recognition, empathy, and ToM), and if so, they have only targeted affective SC components such as emotion recognition, emotion regulation or affective ToM (i.e., mental state decoding). ToM, a key component of SC, has been shown to be severely impaired in individuals with AUD (Bora & Zorlu, 2017), but only one prior fMRI study has investigated affective and cognitive ToM performances in FH+ individuals (Schmid et al, 2023). This study reported higher brain activation in the left insula and inferior frontal cortex in FH+ compared with FH− individuals.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Few studies have explored common SC components (i.e., emotion recognition, empathy, and ToM), and if so, they have only targeted affective SC components such as emotion recognition, emotion regulation or affective ToM (i.e., mental state decoding). ToM, a key component of SC, has been shown to be severely impaired in individuals with AUD (Bora & Zorlu, 2017), but only one prior fMRI study has investigated affective and cognitive ToM performances in FH+ individuals (Schmid et al, 2023). This study reported higher brain activation in the left insula and inferior frontal cortex in FH+ compared with FH− individuals.…”
Section: Discussionmentioning
confidence: 76%
“…an interest in affective and low-level SC processes while affective and higher order SC processes have remained largely unexplored. To fill this gap of the literature, our team recently conducted an fMRI study investigating both, affective and cognitive SC processes, in FH+ adults through a ToM task requiring high-level mental state reasoning (Schmid et al, 2023). The results highlighted differences in terms of neural activations between the FH+ and FH− groups during affective ToM processing in the left insula and inferior frontal cortex.…”
Section: Introductionmentioning
confidence: 99%